Relationship of the Knowledge-Attitudes of Sun Exposure and Physical Activity in Asthma and Non-Asthma: Hubungan Pengetahuan-Sikap Terhadap Paparan Sinar Matahari dan Aktivitas Fisik pada Asma dan Non-Asma - Lorensia, Amelia; Suryadinata, Rivan Virlando; Amir, Gabriella Ayuni; Saputra, Rifaldi (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2024)
Asthma has become a health problem in the world. Asthma symptoms are associated with low vitamin D levels in the body, which increase the risk of an asthma attack. Physical activity is one of the factors that influence vitamin D levels. The purpose was analyzing relationship knowledge-attitude of sun exposure to physical activity in asthma and non-asthma. The study was conducted from March to June 2018. The research design was observational with purposive sampling. Research subjects were > 18 yr did not have other co-morbidities. The results showed that most subjects had high knowledge of sun exposure related to vitamin D in asthma (73.08 %) and non-asthma (84.62 %). In addition, most asthma subjects had a poor attitude (96.15 %), and in non-asthma, all had a poor attitude. There was no correlation between knowledge of sun exposure and physical activity level, both in the asthma group (P (0.657) > 0.05) and non-asthma (P (0.109) > 0.05). There was a relationship between attitudes of sun exposure and physical activity in asthma group (P (0.000) < 0.05), but in a non-asthma group, it could not be analyzed because all had a poor attitude. So that knowledge and attitudes of sun exposure must be increased to support sufficient physical activity.